Pengaruh Konsentrasi Pupuk Organik Cair Asal Buah-Buahan terhadap Pertumbuhan dan Hasil Tanaman Cabai pada Tanah Gambut - Wijaya, Indra; Susana, Rini; Patriani, Patriani (Perkebunan dan Lahan Tropika, 2024)
Chili is one of the horticultural commodities that has a lot of nutrients and vitamins. Generally chili need sufficient nutrients in their growth and development so that the results can be maximized. Nutrients in the soil can not fully meet the needs of plant nutrients so that the addition of nutrients is required through liquid organic fertilizers from fruits. This research aims to determine the best concentration of liquid organic fertilizer from fruits on the growth and yield of chili plants on peat soil. This research was carried out in the experimental field of the Agriculture Faculty, Tanjungpura University Pontianak, in November 2017 to February 2018. This research used a Completely Randomized Design (CRD), with 5 treatment levels, namely k1 (5 ml /l), k2 (20 ml/l), k3 (35 ml/ l), k4 (50 ml/l), k5 (65 ml/l). Each treatment was repeated 5 times with 4 plants sample. Variables observed in this research include plant height, flowering time, plant dry weight, fruit length, fruit diameter, number of fruits, and weight of fruit per plant. The results of this research is the concentration of liquid organic fertilizer from the best fruits not found in this research but the concentration of 65 ml/l of liquid organic fertilizer can increase the growth and yield of chili plants on peat soil.